STRATEGI PENINGKATAN MUTU PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR (PEMP) DI KABUPATEN MALUKU TENGGARA - Bandjar, Sitti Bulkis; Kolopaking, Lala M.; Baga, Lukman M. (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2013)
PEMP Program in Sub-province South East Moluccas is executed since 2001-2007 expected can give positive result to coastal community and small islands especially to fisherman community. The objective of this research is evaluate the sustainable status of PEMP program and identify the performance elements that have an effect on to PEMP program execution so it can be formulated the policy strategy of marine and fisheries development of Sub-province South East Moluccas. The result of this research indicates that program performance in totally pertained “enough” based on RAPFISH analysis. Based on Analytical Hierarchy Process (AHP) result there are fourth criterions that must be paid attention that are (1) PEMP program planning base on society aspect, (2) PEMP program socialization aspect, (3) PEMP program companion execution aspect, and (4) PEMP program execution evaluation aspect. From those fourth criterions, there are five alternatives of policy strategies that ought to conducted by local government of Sub-province South East Moluccas in exploiting PEMP program, that are (1) Strategy of institute reinforcement policy PEMP and human resources, (2). Strategy fund sharing policy from Government of Sub-province South East Moluccas, (3). Strategy of community participation quality improvement policy, (4) Strategy of system structuring current fund returns policy, and (5) Strategy of partnership development policy.Keywords: strategy, quality improvement, coastal community economy empowerment program.